Controlling exciton distribution in WS2 monolayer on a photonic crystal - Zhang, Xiu; Chen, Zhenshi; Liu, Dong; Wan, Lei; Ma, Xuekai; Gao, Tingge (Applied Physics Express)

Dynamics of phase defects trapped in optically imprinted orbits in dissipative binary polariton condensates - Wingenbach, Jan; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

The Ruelle zeta function at zero for nearly hyperbolic 3-manifolds - Cekić, Mihajlo; Delarue, Benjamin; Dyatlov, Semyon; Paternain, Gabriel P. (Inventiones mathematicae)
Abstract We show that for a generic conformal metric perturbation of a compact hyperbolic 3-manifold $$Σ $$ Σ with Betti number $$b_1$$ b 1 , the order of vanishing of the Ruelle zeta function at zero equals $$4-b_1$$ 4 - b 1 , while in the hyperbolic case it is equal to $$4-2b_1$$ 4 - 2 b 1 . This is in contrast to the 2-dimensional case where the order of vanishing is a topological invariant. The proof uses the microlocal approach to dynamical zeta functions, giving a geometric description of generalized Pollicott–Ruelle resonant differential forms at 0 in the hyperbolic case and using first variation for the perturbation. To show that the first variation is generically nonzero we introduce a new identity relating pushforwards of products of resonant and coresonant 2-forms on the sphere bundle $$SΣ $$ S Σ with harmonic 1-forms on $$Σ $$ Σ .
Keywords: General Mathematics

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of curing-induced pre-deformations on the mechanical properties of adhesively bonded joints in steel-intensive mixed-material structures - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Early time behavior of spatial and momentum anisotropies in kinetic theory across different Knudsen numbers - Borghini, Nicolas; Borrell, Marc; Roch, Hendrik (arXiv:2201.13294)
We investigate the early time development of the anisotropic transverse flow and spatial eccentricities of a fireball with various particle-based transport approaches using a fixed initial condition. In numerical simulations ranging from the quasi-collisionless case to the hydrodynamic regime, we find that the onset of $v_n$ and of related measures of anisotropic flow can be described with a simple power-law ansatz, with an exponent that depends on the amount of rescatterings in the system. In the few-rescatterings regime we perform semi-analytical calculations, based on a systematic expansion in powers of time and the cross section, which can reproduce the numerical findings.

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Even anisotropic-flow harmonics are from Venus, odd ones are from Mars - Bachmann, Benedikt; Borghini, Nicolas; Feld, Nina; Roch, Hendrik (arXiv:2203.13306)
We test the ability of the "escape mechanism" to create the anisotropic flow observed in high-energy nuclear collisions. We compare the flow harmonics $v_n$ in the few-rescatterings regime from two types of transport simulations, with $2→ 2$ and $2→ 0$ collision kernels respectively, and from analytical calculations neglecting the gain term of the Boltzmann equation. We find that the even flow harmonics are similar in the three approaches, while the odd harmonics differ significantly.

Linearly shifting ferromagnetic resonance response of La0.7Sr0.3MnO3 thin film for body temperature sensors - Hou, W; Yao, Y; Li, Y; Peng, B; Shi, K; Zhou, Z; Pan, J; Liu, M; Hu, J (Frontiers of materials science)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)

Pattern formation in a four-ring reaction-diffusion network with heterogeneity. - Hunter, I; Norton, MM; Chen, B; Simonetti, C; Moustaka, ME; Touboul, J; Fraden, S (Phys Rev E)

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Losing What You Never Had - Akkerman, Agnes; Manevska, Katerina; Thommes, Kirsten; Sluiter, Roderick (Employment Relations as Networks)

Investigation of leak tightness for bonded steel joints induced by mechanical and corrosive load for use in battery housings - Schmolke, Tobias; Meschut, Gerson (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Three Layers of Abstraction—A Conceptual Framework for Theorizing digital Multi-Sided Platforms - Poniatowski, Martin; Lüttenberg, Hedda; Beverungen, Daniel; Kundisch, Dennis (Information Systems and e-Business Management, Special Issue on Platform Business Models and Platform Strategies)

Property-Driven Testing of Black-Box Functions - Sharma, Arnab; Melnikov, Vitaly; Hüllermeier, Eyke; Wehrheim, Heike (Proceedings of the 10th IEEE/ACM International Conference on Formal Methods in Software Engineering (FormaliSE))
Testing is one of the most frequent means of quality assurance for software. Property-based testing aims at generating test suites for checking code against user-defined properties. Test input generation is, however, most often independent of the property to be checked, and is instead based on random or user-defined data generation.In this paper, we present property-driven unit testing of functions with numerical inputs and outputs. Alike property-based testing, it allows users to define the properties to be tested for. Contrary to property-based testing, it also uses the property for a targeted generation of test inputs. Our approach is a form of learning-based testing where we first of all learn a model of a given black-box function using standard machine learning algorithms, and in a second step use model and property for test input generation. This allows us to test both predefined functions as well as machine learned regression models. Our experimental evaluation shows that our property-driven approach is more effective than standard property-based testing techniques.

Model-driven Continuous Experimentation on Component-based Software Architectures - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Proceedings of the 18th International Conference on Software Architecture Companion)
To build successful software products, developers continuously have to discover what features the users really need. This discovery can be achieved with continuous experimentation, testing different software variants with distinct user groups, and deploying the superior variant for all users. However, existing approaches do not focus on explicit modeling of variants and experiments, which offers advantages such as traceability of decisions and combinability of experiments. Therefore, our vision is the provision of model-driven continuous experimentation, which provides the developer with a framework for structuring the experimentation process. For that, we introduce the overall concept, apply it to the experimentation on component-based software architectures and point out future research questions. In particular, we show the applicability by combining feature models for modeling the software variants, users, and experiments (i.e., model-driven) with MAPE-K for the adaptation (i.e., continuous experimentation) and implementing the concept based on the component-based Angular framework.
Keywords: continuous experimentation; model-driven; component-based software architectures; self-adaptation

„Beim Ausschneiden zeigen die Wörter mir ihre Bestandteile.“ Memoria als Deutungsöffnung bei Herta Müller - Kißling, Magdalena (Der Deutschunterricht (1))